XIAP Knockdown in Alcohol-Associated Liver Disease Models Exhibits Divergent in vitro and in vivo Phenotypes Owing to a Potential Zonal Inhibitory Role of SMAC - He, Li; Sehrawat, Tejasav S.; Verma, Vikas K.; Navarro-Corcuera, Amaia; Sidhu, Guneet; Mauer, Amy; Luo, Xin; Katsumi, Tomohiro; Chen, Jingbiao; Shah, Soni; Arab, Juan Pablo; Cao, Sheng; et al. (Frontiers in Physiology, 2021)
Alcohol-associated liver disease (ALD) has been recognized as the most common cause of advanced liver disease worldwide, though mechanisms of pathogenesis remain incompletely understood. The X-linked inhibitor of apoptosis (XIAP) protein was originally described as an anti-apoptotic protein that directly binds and inhibits caspases-3, 7, and 9. Here, we investigated the function of XIAP in hepatocytes in vitro using gain and loss-of-function approaches. We noted an XIAP-dependent increase in caspase activation as well as increased inflammatory markers and pro-inflammatory EV release from hepatocytes in vitro. Primary hepatocytes (PMH) from XiapAlb.Cre and XiaploxP mice exhibited higher cell death but surprisingly, lower expression of inflammation markers. Conditioned media from these isolated Xiap deleted PMH further decrease inflammation in bone marrow-derived macrophages. Also, interestingly, when administered an ethanol plus Fas-agonist-Jo2 model and an ethanol plus CCl4 model, these animals failed to develop an exacerbated disease phenotype in vivo. Of note, neither XiapAlb.Cre nor XiapAAV8.Cre mice presented with aggravated liver injury, hepatocyte apoptosis, liver steatosis, or fibrosis. Since therapeutics targeting XIAP are currently in clinical trials and caspase-induced death is very important for development of ALD, we sought to explore the potential basis of this unexpected lack of effect. We utilized scRNA-seq and spatially reconstructed hepatocyte transcriptome data from human liver tissue and observed that XIAP was significantly zonated, along with its endogenous inhibitor second mitochondria-derived activator of caspases (SMAC) in periportal region. This contrasted with pericentral zonation of other IAPs including cIAP1 and Apollon as well as caspases 3, 7, and 9. Thus providing a potential explanation for compensation of the effect of Xiap deletion by other IAPs. In conclusion, our findings implicate a potential zonallydependent role for SMAC that prevented development of a phenotype in XIAP knockout mice in ALD models. Targeting SMAC may also be important in addition to current efforts of targeting XIAP in treatment of ALD.